Sosialisasi Fisioterapi mengenai Senam Pencegahan Osteoarthritis terhadap Anggota TNI AU di RSAU dr. M. Salamun - Ika Rahman; Abdul Qudus; Irda Sari; Dhiva Sevia; Rivan Tauvik; Rina Hamidah (LPPM Politeknik Piksi Ganesha, 2023)
Osteoarthritis(OA) is a degenerative disease that often causes pain andlimited movement, especially in the knee joints. One of the prevention effortsis through education and physical exercise such as preventive exercisesfor osteoarthritis. This community service activity aimed to increase the knowledge and awareness of Indonesian Air Force members at the Dr. M. Salamun Air Force Hospitalregarding the importance of physiotherapy in preventing OA, as well as teaching simpleexercises that can be done independently. The implementation method consisted oflectures, discussions, and exercise demonstrations during two meetings. The resultsof the activity showed high enthusiasm from the participants, with increasedactive participation in the exercise activities and understanding of the benefits ofOA prevention. This activity is expected to improve healthy living behaviorsand awareness among TNI members regarding the importance of preventing-musculoskeletal disorders from an early age.